Pembuatan Sistem Monitoring Temperatur, pH dan Salinitas Tambak Ikan Secara Nirkabel - Arfan Eko Fahrudin; Said Ja'far Shadiq; Ade Agung Harnawan (Lambung Mangkurat University Press, 2019)
− The quality of water hold on important rule in the field of fisheries, especially in cultivation activities. Parameters of water quality are often observed such as temperature, pH, salinity, and others. The influence of water quality on cultivation activity is very important therefore supervision of water quality parameters is absolute done by cultivators. This research had created the quality of water monitoring system in fishponds wirelessly. The system consist of the transmitter that integrated with LM35 sensor, pH meter kit sensor and conductivity sensor as measurer of water quality, and the receiver receive datum transmitted wirelessly with nRF24L01 module a long 5 meters distance from transmitter. The receiver equipped with an interface with PC which can save data measurement automatically to Microsoft Excel. The results of the validation of the measurement instrument obtained average of error relative to measurement were 0.01 0C for temperature, 0.005 for pH and 0.008 ppt for salinity. In summary, the measurement of water quality in surface water fishponds of temperature is 29oC until 38oC, pH is 8,6 until 11,9 and salinity is 12 until 21 ppt.